ДИДАКТИЧНІ УМОВИ ЗАСТОСУВАННЯ ІНФОРМАЦІЙНИХ ТЕХНОЛОГІЙ У ПРОЦЕСІ НАВЧАННЯ СТУДЕНТІВ ВУЗУ (Педагогіка вищої та середньої школи, 2009)
In the article the methods and complex of didactic conditions of information technology appliance in the educational process of students in a higher educational establishment have been elaborated and represented.